Journal of Biogeography (Oxford Blackwell Scientific Publications Ltd, 1987)
covers the topic what is naturalness?debates on both philosophy and methods, the implecations of ecosystem fragmentation, the impact of human-induced changes,as well as ecological and econimic significance of biodiversity. All systematic groups are embraced, from theory to practice, from plant to animal.
Keywords: geography